The economics of e-commerce and the internet - Deak, Edward J. (Thomson Learrning, 2003)
This book provides an economic analysis of e-commerce and the Internet. The book takes a broad approach in looking at the microeconomic structure, competitive strategy and efficiency, as well as social and legal implications of the e-commerce revolution. The unique approach of the book is its demonstration of economic tensions, economic forces acting in concert or in opposition, that are consistently affecting the continuing development of e-commerce.